Exploring Translanguaging Practices in a Secondary EFL Classroom - Khoirunisa, Salma; Nugraha, Sidik Indra; Wachyudi, Kelik (PROJECT (Professional Journal of English Education), 2026)
This research investigates how translanguaging is practiced in a secondary EFL classroom and how it affects students’ comprehension and participation. A qualitative method was used, involving classroom observations and interviews with one English teacher and students. The findings show that translanguaging was used intentionally through code-switching, translation, and interpreting to explain materials, clarify instructions, and manage classroom interaction. Students also used Indonesian during group discussions and switched to English when presenting their work. The results further reveal that translanguaging improved students’ comprehension by making input more understandable and reducing confusion. It also increased participation and confidence, especially among lower-proficiency students, as they felt more comfortable expressing ideas using both languages. Therefore, translanguaging serves as an effective pedagogical strategy in EFL classrooms when applied purposefully. Future research is suggested to explore its long-term impact on language proficiency.